TRANSFORMASI ORNAMEN RUMOH ACEH TEUNGKU CHIK AWEE GEUTAH PADA RAPA’I ACEH - M Hamzah (Melayu Arts and Performance Journal, 2018)
ABSTRACT  The ornament of Rumoh Aceh (Aceh’s house) Teungku Chik Awee Geutah is one of the cultural legacies in the form of carving that has been rare to be found on mediums. Based on that phenomenon, the interest of transforming the ornaments on rapa’i has become an idea in the creation of an artwork (craft artwork). The aim of this artwork creation is the personal’s or craftsmen’s and rapa’i art performer’s understanding/realization that the concept of transformation in the cultural treasury is very broad and it’s always available to be studied further for creative work. Besides that, it also develops a cultural heritage by offering the beautiful values of rapa’i and ornament so it can be owned and fancied more by Aceh people. The methods used in the concept of creation consisted of several stages namely the exploration stage, the designation stage, and the embodiment stage. The materials used consisted of tualang wood, bamboo, goatskin, and parchment cowskin. The techniques used in this artwork were bubut technique, low-carving technique, middle-carving technique, and finishing melamine system. The form of artwork created was three-dimensional artwork namely percussion instrument carved with the ornaments of Rumoh Aceh Teungku Chik Awee Geutah transformed on the baloh (frame wall) of rapa’i. Keywords: ornament, rumoh aceh teungku chik awee geutah, rapa’i aceh, transformation    ABSTRAK Ornamen rumoh  Aceh Teungku Chik Awee Geutah merupakan salah satu warisan budaya berupa ukiran yang telah langka ditemukan di media-media. Berdasarkan fenomena tersebut ketertarikan untuk metrasformasikan ornamen pada rapa’i telah menjadikan suatu ide dalam penciptaan sebuah karya seni (seni kriya). Tujuan penciptaan karya adalah untuk memahami/menyadari secara personal maupun para kriawan dan pelaku seni rapa’i bahwa konsep tranformasi pada khasanah budaya sangat luas dan selalu tersajikan untuk ditela’ah dalam berkarya. Selaras dengan itu juga mengembangkan suatu warisan budaya dengan menawarkan nilai keindahan rapa’i dan ornamen untuk dapat lebih dimiliki dan digemari oleh masyarakat Aceh. Metode yang digunakan dalam konsep penciptaan yaitu melalui beberapa tahap, tahap eksplorasi, tahap perancangan, dan tahap perwujudan. Bahan yang digunakan yaitu terdiri dari kayu tualang, bambu, kulit kambing, dan kulit sapi perkamen. Teknik yang digunakan pada karya ini yaitu teknik bubut, teknik ukir rendah, ukir sedang, dan finishing melamine system. Bentuk karya yang diciptakan merupakan karya tiga dimensi yaitu alat musik perkusi yang terukir ornamen Rumoh Teungku Chik Awee Geutah yang ditransformasi pada baloh (dinding frame) rapa’i.